2021
DOI: 10.1177/15333175211006504
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Does Not Increase the Risk of Neurodegenerative Dementia: A Case-Control Study

Abstract: Objective: This study was conducted to evaluate the association between neurodegenerative dementia and herpes zoster infection (HZI) using a national sample cohort. Methods: From the national cohort study conducted by the Korean National Health Insurance Service, we extracted data for patients with neurodegenerative dementia and for 1:4 matched control participants and searched the patient histories for HZI. Results: The adjusted odds ratio (OR) for HZI was 0.90 (95% CI = 0.84-0.97) in the dementia group. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
2
25
6
Order By: Relevance
“…Previous population-based studies report both decreased 12 and increased [13][14][15] risks of dementia after HZ infection. A case-control study from the National Health Insurance Service-National Sample Cohort in South Korea found lower odds of prior HZ (OR 0.91; 95% CI 0.84-0.97) among 11,445 people aged 60 years or older with dementia compared with 45,780 matched controls without dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous population-based studies report both decreased 12 and increased [13][14][15] risks of dementia after HZ infection. A case-control study from the National Health Insurance Service-National Sample Cohort in South Korea found lower odds of prior HZ (OR 0.91; 95% CI 0.84-0.97) among 11,445 people aged 60 years or older with dementia compared with 45,780 matched controls without dementia.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Recent results from a Korean case control study showed no evidence for an association. 14 Subgroup analyses from a multi-centre Northern European cohort focussed on antiviral medication use after herpes viruses also failed to support these findings. 15 It is unclear whether differences between populations or within population subgroups could explain the contrasting findings.…”
Section: Introductionmentioning
confidence: 99%
“…Other research (4) has supported these findings. However, in a case-control study, Choi et al found that HZ did not raise the incidence of dementia (5).…”
Section: Abstract Background/αim: the Relationship Of Herpes Viruses And Herpes Zoster (Hz) With Dementia Andmentioning
confidence: 92%